امتزاز األصبغة الكاتيونية من المحاليل المائية باستعمال الطحالب الخضراء المحسنة بالطين - نور الهدي, حبيب; الشيماء, مصباحي; جهاد, نيد (My University, 2022)
٠ٙذف اٌؼًّ اٌؾبٌٟ، ألعشاء رؼذ٠ ًثاعزخذاَ هؾبٌت فذ٠مخ ٌٍج١ئخ ِٕٚخفنخ اٌزىٍفخ ِغ اٌط١ ٓ اٌغضائشٞ و ّّزبص ِؾزٍّٗ إلصاٌخ فجغخ أصسق اٌّض١ٍ١)ٓBMِ ِٓ (ؾبٌ١ٍٙب اٌّبئ١خ. ؽ١ش ئعزخذِخ رمٕ١بد رؾٍ١ٍ١خ ِخزٍفخ ٌذساعخ: ؽىً اٌغطؼ، ٚثٍٛسح اٌّبدح، ٚاٌّغّٛػخ اٌٛظ١ف١خ ٌىً ِٓ اٌط١ٚ ٓاٌطؾبٌت. رُ ئعشاء رؾغ١ ٓثٛاعطخ رقّ١ ( ُdesign Behnken – Boxٌ (زؾغ١ ٓؽبٌخ اٌزؾّ١( ًرؾّ١ ًاٌطؾبٌت فٟ اٌط١ )ٓثبإلمبفخ ئٌٝ ِزغ١شاد ػٍّ١خ االِزضاص )عشػخ اٌ ّّزضاد، ٚدسعخ اٌؾّٛمخ فٟ اٌّؾٍٛي، ٚدسعخ اٌؾشاسح ٚ ٚلذ اٌزالِظ(. أظٙشد إٌزبئظ اٌزٟ رُ اٌؾقٛي ػٍ١ٙب أْ ٔغجخ ئصاٌخ BM٪( 34.91) ٠ّىٓ رؾم١مٗ ػٓ هش٠ك رؾّ١٪ ً50 ِٓ اٌطؾبٌت فٟ اٌط١ٚ ،ٓثّؼب١٠ش ػٍّ١خ االِزضاص اٌ ّضٍٝ)عشػخ اإلِزقبؿg 05.0 ، 7=pH ،دسعخ اٌؾشاسح C°45ٚ ،لذ اٌزالِظ min 5.32 .)رُ ٚفف ٔزبئظ االِزضاص ثؾىً ع١ذ ثٛاعطخ اٌؾشو١خ ِٓ اٌذسعخ اٌضبٔ١خ، ٚارجغ ِزغبٚٞ االِزضاص والً ِٓ ّٔبرط Freundlich ٚTemkin . رُ اٌؼضٛس ػٍٝ لذسح االِزضاص اٌمقٜٛ (Qmaxٌٍ (طؾبٌت / اٌط١ٌ ٓقجغخ g/mg 5.113.BMٚثبٌزبٌٟ، ٠ ؾ١ش ٘زا اٌؼًّ ئٌٝ أٔٗ ٠ّىٓ ئعزخذاَ اٌطؾبٌت / اٌط١ ٓوّّزبص هج١ؼٟ ٚاػذ ٌقجغخ BM وّٕٛرط ٌٍقجغخ اٌىبر١ٔٛ١خ ِٓ اٌّ١بٖ ٚ ِ١بٖ اٌقشف اٌقؾٟ.In this study، the synthesis of an eco-friendly and Low-cost algae modified Algerian clay and further explored as a potential adsorbent to remove hazardous methylene blue (BM) dye from aqueous solution. Various analytical techniques were used to investigate the surface morphology، material crystallinity، and fundamental functional group of the caly and aLgae. Parametric optimization by Box–Behnken design was made to optimize the synthesis condition (loading clay into algae) in addition to adsorption operation parameters (adsorbent dose، solution pH، temperature، and contact time). The obtained results show that the fast BM removal (91.34%) can be achieved by loading 50% clay into algae، and at optimum adsorption operation parameters (adsorbent dosage of 0.05 g، solution of pH 5، temperature of 45 ◦C، and contact time of 32.5 min). The adsorption resuLts were well described by pseudo- second-order kinetic، and adsorption isotherm was followed both Freundlich and Temkin models. The maximum adsorption capacity (Qmax) of algae /clay for BM dye was found to be 113.5 mg/g. Thus، this work indicates that the algae / clay can be applied as a natural promising adsorbent for BM dye as model of cationic dye from water/ wastewater.
مذكرة ماستر تخصص كيمياء
Keywords: هؾبٌت، اٌط١ ٓاٌغضائشٞ، فجغخ أصسق اٌّض١ٍ١ ، ٓآٌ١خ االِزضاص، ّٔبرط اإل٠ضٚربسَ.; Algae، Algerian clay; Methylene blue dye; Adsorption mechanism; Isotherm models